Room temperature stable twist-bend nematic materials without crystallization over 1 year - Conglong Yuan; Yuxing Zhan; Huixian Liu; Zhaoyi Wang; Ning Shen; Binghui Liu; Honglong Hu; Zhigang Zheng (Giant, 2024)
The twist-bend nematic (NTB) phase of achiral liquid crystals (LCs) manifests a unique self-assembled heliconical structure with nanometer-scale pitch length, mirroring the chiral symmetry-breaking phenomena in nature, thus sparking widespread research interest. However, the ingenious NTB phase is only stable at high temperatures within a very limited temperature interval, often undergoing inevitable crystallization at low temperatures. Herein, room temperature supercooled NTB material systems composed of meticulously designed LC dimer mixtures with varying molecular curvatures and central flexibility were developed, resulting in complete resistance to crystallization even after 1 year of storage. Furthermore, the proposed NTB material systems demonstrated exceptional compatibility with common nematic LCs, facilitating the tailoring of overall physical parameters, particularly to achieve a sufficiently low bend elastic constant with excellent stability. This work represents a paradigmatic advancement forward in realizing stable NTB phase materials with a broad temperature range and resistance to crystallization, thereby tackling the enduring and seemingly insurmountable challenge while providing impetus for further exploration of their applications in soft matter, crystallography, and advanced photonics.